Session-to-session variations of external load measures of youth soccer players in medium-sided games - Clemente, F. M.; Rabbani, A.; Kargarfard, M.; Nikolaidis, P. T.; Rosemann, T.; Knechtle, B. (International Journal of Environmental Research and Public Health, 2019)
The aim of this study was to analyze the variability of time-motion variables during five vs. five games when completed within the same session as, and between, two different sessions. Ten under-19 male soccer players (18.27 ± 0.47 years old) participated in this study. The five vs. five matches (3 × 5 min) were played twice with a 3-day interval of rest in the same week. Moderate between-session variations were observed for TD (total distance) (range coefficient of variation (CV), 6.9; 8.3%, confidence interval (CI), (5.0; 14.0), standardized typical error (STE), 0.68; 1.06, (0.64; 1.75)) and RD (running distance) (range CV, 53.3; 145.7%, (36.6; 338.9), STE, 0.83; 1.09, (0.60; 1.76)). PL (player load) showed small variations (range CV, 4.9; 6.0%, [3.6; 10.1], STE, 0.37; 0.43, (0.27; 0.71)). In within-session analyses for examining the differences between sets, a small decrease was observed in RD in set 3 versus set 2 (-14.8%, 90% CI (-32.1; 6.9%); standardized difference (ES): -0.39 (0.95; 0.16)). TD decreased with moderate (-3.5%, (-6.8; -0.1%); ES: -0.65(-1.30; -0.01)) and large (-8.2%, (-11.4; -4.9%); ES: -1.58(-2.24; -0.92)) effects in sets 2 and 3, respectively, versus set 1. Our results suggest that PL is the most stable performance variable. It was also verified that measures had a progressive decreasing tendency within a session.